IMPLEMENTASI TUJUAN JANGKA MENENGAH PROYEK PERUBAHAN OLEH ALUMNI DIKLAT TINGKAT III POLA BARU (Studi Kasus di Sekretariat Daerah Provinsi Sulawesi Utara) - Fredrik Rotinsulu (Lembaga Administrasi Negara, 2018)
This study is a study focusing on the implementation of Medium-Term Project goals of Change from the three Esalon Officials who have attended the Third Level Leadership Training of New Patterns. This research takes place in North Sulawesi Provincial Secretariat. Research focus on the implementation of intermediate goals of change projects, inhibiting factors, supporting factors. Implementation of the medium-term objectives of the change project in the Provincial Secretariat can be realized due to the commitment of Mentor, Coach, Project Leader During Project Change Seminar. The inhibiting factors in the implementation of mid-term change project objectives within the scope of the North Sulawesi Provincial Secretariat include (1) Moving external stakeholders need time in coordination, (2) The budget for medium-term objectives is not yet embedded in the Bureau's budget, (3) Project Leader is assigned. (4) Not yet mastering foreign languages especially Mandarin. (5) There is a stacholder that does not seriously support the implementation of the change project. Factors supporting stakeholder participation in the implementation program include: (1) Leadership Commitment, (2) Project Leader Cooperation with stakeholders, (3) Governor Regulation No. 25/2016 on Guidance on Case Handling within Local Government North Sulawesi Province.Keywords: Implementation, Stakeholder, Destination of Intermediate Project Steps